Development and validation of self-report Mizaj identification questionnaire Based on Persian Medicine for the elders (age over 60) - Marjan Akhtari; Morteza Mojahedi; Narjes Gorji; Ali Bijani; Seyyed Ali Mozaffarpur; Roshanak Saghebi; Reihaneh Moeini (Caspian Journal of Internal Medicine, 2024)
Background: Introduction: Mizaj is the basis of attention to individual differences in Persian Medicine (PM). Regarding the importance of Mizaj for health preservation and treating diseases, it is necessary to achieve a standard tool for Mizaj identification. The purpose of this study was to design a standard self-reporting Mizaj identification questionnaire for elders. Methods: In this exploratory sequential study, criteria of Mizaj identification were extracted by reviewing PM literatures and interview with PM experts and elders. The primary questionnaire was designed and its validity and reliability were assessed, using weighted Kappa statistics, Pearson correlation coefficient (PCC) assessment, receiver operating characteristic (ROC) curve and determining the specificity and sensitivity of cut-off points. Results: Among the 101 items in the primary questionnaire, 73 items had acceptable reliability. The final 20-item questionnaire was obtained after the criterion validity and PCC assessment. The sensitivity and specificity of this questionnaire were 83% and 88% for warmness, 49% and 80% for moderate in warmness-coldness, 72% and 91% for coldness, 57% and 78% for wetness, 30% and 79% for moderate in wetness-dryness, and 81% and 67% for dryness, respectively. Conclusion: The first standard Mizaj identification questionnaire for elders was designed in this study. It is recommended as a supplementary diagnostic tool for clinicians and researchers in PM. Also, the people with age over 60 can use it to identify their own Mizaj and then, choose the suitable PM or Unani medicine lifestyle recommendations based on their Mizaj.